Application of usability testing for analyzing the quality of 'Keluarga' pharmacy system in Pekanbaru - M. Khairul Anam; muhammad Fuad; Helda Yenni; Syarifah Eiva Fatda; Hadi Asnal; Hamdani Hamdani (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
Family Pharmacy is a line of business that sells medicines in the city of Pekanbaru. Drug sales at these pharmacies are carried out offline by directly coming to the pharmacy and online through the Family Pharmacy application which can be downloaded via the google play store. However, the facilities offered by the Family Pharmacy application have not been able to provide user satisfaction, so that it has not fulfilled the initial goal of making the application, namely being able to increase drug sales and obtain a high level of satisfaction. Therefore, the author took the opportunity to conduct research in order to determine the quality of the application using the usability testing method. The analysis of the Family Pharmacy application aims to find out the shortcomings of the application that has been built, both in terms of learnability, efficiency, memorability, error, and satisfaction. The results obtained that the family pharmacy application has good quality according to users with 72.5% learnability, 74.2% efficiency, 74.4% memorability, 70.1% errors, and 71.4% satisfaction. However, the weakness of the Family Pharmacy application is that the majority of Family Pharmacy customers do not know about the Family Pharmacy application.